Laelapidae (Acari: Mesostigmata) on megachiropteran bats: new records and a new species of Neolaelaps Hirst - Shaw, Matthew D. (Zootaxa, 2011)
The little-known monotypic genus Notolaelaps is newly recorded from Australia. Males of Notolaelaps novaguinea Womersley are fully described for the first time, protonymphs are newly described, and females redescribed. A fourth species of Neolaelaps, Ne. windsori sp. nov., previously regarded as a form of Neolaelaps vitzthumi Domrow, is described as new. Male Neolaelaps vitzthumi are described for the first time from a heavily-infested specimen of Pteropus alecto. Both genera are re-diagnosed. Relationships between Notolaelaps, Neolaelaps and the Macronyssidae are discussed.